Structural investigation of Pb(Mo@@ xW1-@@ x)O4 solid solutions via X-ray and neutron diffraction. (June 2016) - Kuz'micheva, G.M.; Kaurova, I.A.; Brykovskiy, A.A.; Rybakov, V.B.; Gorobets, Yu. N.; Shekhovtsov, A.N.; Cousson, A.
Graphical abstract: Highlights: PbMo @@x W1- @@ x O4 crystals with @@ x = 0.2, 0.5, 0.8 were grown by Czochralski method. The real crystal structures were refined by neutron and X-ray diffraction. Introduction of YNbO4 into charge contributes to growth of colorless crystals. Nb and Y contents as well as O vacancies content increase with increasing @@ x . Correlation between cell parameters, cation content, and O vacancies was revealed. Abstract: PbMo @@x W1- @@ x O4 single-crystal solid solutions with @@ x = 0.2, 0.5, 0.8 have been grown by the Czochralski method in air atmosphere from the initial charge with over-stoichiometric amount of YNbO4 (15 wt%). X-ray and neutron single-crystal and X-ray powder (Rietveld method) diffraction investigations of PbMo @@x W1- @@ x O4 crystals indicate bulk inhomogeneity of their compositions, absence of color centers, and deviation of refined compositions from initial ones: the Nb 5+ and Y 3+ contents as well as oxygen vacancies content increase with increasing @@ x in PbMo @@x W1- @@ x O4 . It was found that PbMo @@x W1- @@ x O4 with @@ x = 0.2, 0.5, 0.8, 1.0 crystallizes in the scheelite-type structure with space group @@ I 41 @@ /a, unlike crystal with @@ x = 0, which is characterized by the symmetry reduction to space group I 4 _ caused by ordering of oxygen vacancies. The correlation between the @@ a and @@ c unit cell parameters and composition of cation sites, dodecahedral and tetrahedral, and deficiency of oxygen site was revealed.